Anti-glomerular basement membrane nephritis with bronchial carcinoma: a case report. Issue 3 (October 2020) - Gao, Chenni; Xie, Jingyuan; Pan, Xiaoxia; Chen, Xiaonong
Renal insufficiency is common among patients with various types of malignant tumors. However, the occurrence of anti-glomerular basement membrane (GBM) nephritis in a patient with a malignant tumor is relatively rare. Here, we describe a patient with bronchial carcinoma who exhibited acute kidney injury, hematuria, and non-nephrotic-range proteinuria. The patient had positive serum anti-GBM antibody findings and biopsy-proven anti-GBM nephritis. This is a rare instance of anti-GBM nephritis in a patient with a malignant solid tumor. Neoplasia was presumed to contribute to the development of anti-GBM nephritis through secretion of tumor-related antigens or unusual exposure to GBM.